A new self-compatibility haplotype in the sweet cherry 'Kronio', S5', attributable to a pollen-part mutation in the SFB gene - Marchese, Annalisa (Journal of experimental botany, 2007)
'Kronio' is a Sicilian cultivar of sweet cherry (Prunus avium), nominally with the incompatibility genotype S(5)S(6), that is reported to be naturally self-compatible. In this work the cause of its self-compatibility was investigated. Test selfing confirmed self-compatibility and provided embryos for analysis; PCR with consensus primers designed to amplify S-RNase and SFB alleles showed that the embryos were of two types, S(5)S(5) and S(5)S(6), indicating that S(6) pollen failed, but S(5) succeeded, perhaps because of a mutation in the pollen or stylar component. Stylar RNase analysis indicated active S-RNases for both S(5) and S(6). The S-RNase alleles were cloned and sequenced; and sequences encode functional proteins. Cloning and sequencing of SFB alleles showed that S(6) was normal but S(5) had a premature stop codon upstream of the variable region HVa resulting in a truncated protein. Therefore, the self-compatibility can be attributed to a pollen-part mutation of S(5), designated S(5)', the first reported case of breakdown of self-incompatibility in diploid sweet cherry caused by a natural mutation at the S-locus. The second intron of the S-RNase associated with S(5)' contained a microsatellite smaller than that associated with S(5); primers designed to amplify across this microsatellite effectively distinguished S(5) from S(5)'. Analysis of some other Sicilian cherries with these primers indicated that S(5)' is also present in the Sicilian cultivar 'Maiolina a Rappu', and this proved to be self-compatible